Development of alternatives for accelerating structure in the range of intermediate proton energy - Bomko, V.A.; Egorov, A.M.; Kobets, A.P.; Marinina, E.D.; Rudiak, B.I.; Tishkin, S.S.; Vdovin, S.A.; Zaitsev, B.V. (Вопросы атомной науки и техники, 2004)
A scope of the linear accelerating structures for acceleration proton high rower beams in energy range 5…
100 MeV is presented. Main task lies in a possibility to use superconductive equipment. The results are given for
+original desgn of accelerating structures of alternating segments being excited on E11-wave on π/2-mode. A possibility is discussed about the use of focusing blocks with the RF–quadrupoles which uniformly fit into the chain of
accelerating cells. Приводиться огляд розробок конструкцій структур лінійних прискорювачів протонів з високою
потужністю пучка в діапазоні енергій 5...100 МеВ. Основна вимога полягає в можливості використання
надпровідної техніки. Описані результати оригінальних розробок прискорюючої структури типу зустрічних
сегментів, що збуджується на Е11-хвилі, а також можливість застосування фокусуючих блоків з ВЧ-квадруполями, які однорідно вписуюються в цепочку прискорюючих комірок. Приводится обзор разработок конструкций структур линейных ускорителей протонов с большой мощностью пучка в диапазоне энергий 5...100 МэВ. Главная задача заключается в возможности использования сверхпроводящей техники. Описаны результаты оригинальных разработок ускоряющей структуры типа встречных
сегментов, возбуждаемой на Е11-волне, и возможность применения фокусирующих блоков с ВЧ – квадруполями, которые однородно вписываются в цепочку ускоряющих ячеек.